Development of Mycobacterium culture at Medical Laboratory, Khon Kaen Hospital - Srisurat, Nuttiya; Wattanavises, Sasiprapa; Suwansirikul, Natthanit (Journal of Health Science of Thailand, 2017)
The objective of this study was to determine the combination of solid (Lowenstein-Jensen medium- LJ medium) and liquid media (Mycobacterium growth indicator tube - MGIT) in addition to MTT assay (3-4,5 dimethylthiazol-2-yl-2,5-diphenyl tetrazolium bromide) to increase positive rate of Mycobacteria detection and reduce turnaround time of Mycobacterium culture. A total of 2,572 clinical specimens, requested for Mycobacterium culture in KhonKaen Hospital from March 2009 to December 2012 were cultured on solid and liquid media and then tested for anti-TB susceptibility test by using MTT method. The liquid media was evaluated and compared with solid media for recovery of Mycobacteria in terms of positive rate and detection time. To evaluate the performance of MTT method for first-line drugs susceptible to Mycobacterium tuberculosis and compared to proportion method. The results showed that positive rate of Mycobacteria detection was increase from 4.3% to 19.5% when combined the culture on solid and liquid media. A total of 151 samples were tested for the presence of Mycobacteria were analysis; The mean time to detection was 16 days (range 3 - 38 days) with liquid media, while 37 days (range 10 - 63 days) with solid media. The recovery rate of Mycobacteria was 98.7% (149/151) on liquid media and 21.9% (33/151) on solid media. The results of rifampicin, isoniazid, ethambutal and streptomycin resistance to Mycobacterium tuberculosis by using MTT and proportion method, showed a high level of agreement with 96.9% (63/65), 95.4% (62/65), 93.8% (61/65) and 98.5% (64/65), respectively. Inconsistent results of two methods was 12.3% (8/65), these 66.7% (4/6) was the multidrug-resistant tuberculosis (MDR-TB), while 6.8% (4/59) was the Non-MDR-TB. Conclusions: the liquid media has better recovery rate and reduce time to detection of Mycobacteria. In addition to using MTT method, the turnaround time of Mycobacterium culture was reduced from 7 months (121 - 301 days) to 1.4 months (20 - 79 days).